SELF-DEVELOPMENT OF PERSONALITY AND SELF-EDUCATIONAL ACTIVITY OF THE STUDENT (Pedagogy of Higher and Secondary Education, 2022)
The problem of personalities' self-development and students' self-educational activity is considered in the article. The essence of notions "self-development", "self-education".
Keywords: educational activity; self-development; self-education; personality